2020
DOI: 10.1177/1078155220907650
|View full text |Cite
|
Sign up to set email alerts
|

Managing chemotherapy-related toxicities in the community setting: A survey of pharmacists in Ontario

Abstract: Background: Toxicity management is a challenge with cancer treatment, including oral anticancer drugs. A review of claims data showed that a majority of publically funded oral anticancer drugs were filled in the community where pharmacists may not necessarily possess the specialized knowledge, skills, and experience required to provide effective patient care. A survey of community pharmacists in Ontario was conducted to identify the behaviours and preferences of community pharmacists specific to the management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…This finding is similar to that of a Canadian study that showed that 77% of community pharmacists identified the insufficiency of their oncology training to manage toxicities related to oral anticancer medicines. 31 The finding is also consistent with that of Abbott et al who reported that 67.6% of community pharmacists felt that they did not receive adequate knowledge on cancer treatments through CPDs or undergraduate training. 23 Furthermore, the current study showed that readiness score was significantly higher among respondents who reported adequacy of content related to OAMs during undergraduate training.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is similar to that of a Canadian study that showed that 77% of community pharmacists identified the insufficiency of their oncology training to manage toxicities related to oral anticancer medicines. 31 The finding is also consistent with that of Abbott et al who reported that 67.6% of community pharmacists felt that they did not receive adequate knowledge on cancer treatments through CPDs or undergraduate training. 23 Furthermore, the current study showed that readiness score was significantly higher among respondents who reported adequacy of content related to OAMs during undergraduate training.…”
Section: Discussionsupporting
confidence: 90%
“…However, pharmacists and pharmaconomists stated that it was important to gain more knowledge about cancer treatment in order to counsel cancer patients/survivors at the community pharmacy. Pharmacy staff's knowledge could be improved through undergraduate oncology education and intensive continuous education programs [41,42]. Currently, oncology education for pharmacists or pharmaconomists does not exist in Denmark.…”
Section: Discussionmentioning
confidence: 99%